Alzheimer's disease and gut-brain axis: Drosophila melanogaster as a model - Alves, Samuel de Mattos; Lisboa-Filho, Paulo Noronha; Zilli Vieira, Carolina Letícia; Piacenti-Silva, Marina (Frontiers in Neuroscience, 2025)
Research indicates that by 2050, more than 150 million people will be living with Alzheimer's disease (AD), a condition associated with neurodegeneration due to the accumulation of amyloid-beta and tau proteins. In addition to genetic background, endocrine disruption, and cellular senescence, management of the gut microbiota has emerged as a key element in the diagnosis, progression, and treatment of AD, as certain bacterial metabolites can travel through the bloodstream and cross the blood-brain barrier. This mini-review explores the relationship between tau protein accumulation and gut dysbiosis in Drosophila melanogaster. This model facilitates the investigation of how gut-derived metabolites contribute to neurocognitive impairment and dementia. Understanding the role of direct and indirect bacterial by-products, such as lactate and acetate, in glial cell activation and tau protein dynamics may provide insights into the mechanisms of AD progression and contribute to more effective treatments. Here we discuss how the simplicity and extensive genetic tools of Drosophila make it a valuable model for studying these interactions and testing potential therapeutics, including probiotics. Integrating Drosophila studies with other established models may reveal conserved pathways and accelerate the translation of findings into clinical applications.